Sentiment Analysis of Augmented Reality Smart Tour Guide Apps in India - Mahajan, Arvind; Kumar, Sunil (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The invention in technology is underway, register human tour guides are short in supply at cultural heritage destinations during the season. Augment Reality (AR) apps such as smart tour guide apps which are useful for the tourist to enhance tour experience by using AR technology apps. Does the such app fulfil the users need? The purpose of this paper is to do comparative analysis of the "Trip My Way App" and the "Pinakin App" smart guide apps in India and use of smart technology in tourism. This is an exploratory qualitative study conducted by applying comparative research approach. This study compares 18 identified features described by app providers, such as information quality, ease of use, perceived usefulness and so on in app information. The findings of the study will assist app developers to do improvement in the apps. User generated content are useful to resolve technical and other issues face by users. Provider can use machine learning software to do sentiment analysis.